urgent

Asked by 2806rahul | 30th May, 2010, 09:28: AM

Expert Answer:

Dear Student,

p(x) + q(y) = p - q.................(1)

q(x) - p(y) = p + q.................(2)

multiply eqn(1) by p and eqn(2)  by q

p2x+pqy = p2-pq...............(3)

q2x-pqy = pq+q2 ..............(4)

eqn(3)+eqn(4)

=> (p2+q2)x = (p2+q2)

=> x=1

substitutin this value in eqn(1)

y= - 1

Regards Topperlearning.

 

Answered by  | 30th May, 2010, 10:15: AM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.